The Analysis of Locutionary, Illocutionary, and Perlocutionary of Speech Acts in the Short Story "Rembulan dalam Cappuccino" by Seno Gumira Ajidarma - Julisah Izar; Muhammad Muslim Nasution; Olivia Virginia; Neldi Harianto (JETLi: Journal of English Teaching and Linguistics, 2022)
The aims of this research are to analyze and to identify the forms of locutionary, illocutionary, and perlocutionary of speech acts in “Rembulan dalam Cappuccino” short story by Seno Gumira Ajidarma. The locutionary, illocutionary, and perlocutionary of speech acts are the scope of Pragmatics where we know, one of the fields of linguistics that studies language along with its context is also called pragmatics. Basically, pragmatics is a scientific study that studies how a language is used in communication. In contrast to linguistics which studies and discusses the structure of language internally, pragmatic studies examine the meanings of external lingual units. The approach used in this research is qualitative approach with a pragmatic study. Then, the research method used in this research is a qualitative descriptive method. The data and data sources used in this study is “Rembulan dalam Cappuccino” short story by Seno Gumira Ajidarma, and other sources such as books, articles, journals, and previous research that related to the locutionary, illocutionary, and perlocutionary of speech acts study. The data collection technique that writer used is library research, with data analysis technique in the form of identifying and classifying data, analyzing and presenting data, and conclusion or verification. The result showed that there were 15 dialogues that contain types of locutionary, illocutionary, and perlocutionary of speech acts from a total of 25 dialogues in that short story. As many as 13 dialogues that containing the type of locutionary, 15 dialogues that containing the types of illocutionary, and 1 dialogue which is a type of perlocutionary of speech acts.